Great poets of the romantic age - Sheen, Michael (NAXOS AudioBooks, 1994)
Includes selections from William Blake, William Wordsworth, Percy Bysshe Shelley, Lord Byron, John Keats, and others
Compact discs. - Program notes inserted in container
Read by Michael Sheen
Selected by Heather Godwin ; Produced by Nicolas Soames ; Post-production Simon Weir, The Classical Recording Company ; Engineer (speech) Alan Smyth, Bucks Audio Cassettes
The tyger ; Introduction ; The lamb ; Introduction ; Earth's answer ; The sick rose ; Auguries of innocence ; Night ; Love's secret ; Jerusalem / William Blake -- I wandered lonely as a cloud ; Ode, Intimations of immortality ; Expostulation and reply ; The tables turned ; Tintern Abbey ; The world ; The solitary reaper ; The rainbow ; Perfect woman ; To my sister / William Wordsworth -- Ozymandias ; Ode to the west wind ; To Jane: the invitation ; The moon ; To a skylark ; Sonnet ; From Epipsychidion (Three sermons on free love ; The annihilation of love) / Percy Bysshe Shelley -- To autumn ; Ode on a Grecian urn ; La belle dame sans merci ; From Endymion ; Ode on melancholy ; Fancy ; Ode to a nightingale / John Keats -- When we two parted ; She walks in beauty ; The destruction of Sennacherib ; One struggle more, and I am free ; From Don Juan ; We'll go no more a-roving / Lord Byron -- The peasant poet ; I am / John Clare -- Kubla Khan. The rime of the ancient mariner / Samuel Taylor Coleridge
Keywords: Geschichte 1800-1900; English poetry / 19th century; Romanticism / Great Britain; Großbritannien